1999
DOI: 10.1128/aac.43.7.1674
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity of the Reverse Transcriptase of Human Immunodeficiency Virus Type 1 from Untreated Brazilian Individuals

Abstract: The presence of human immunodeficiency virus type 1 (HIV-1) bearing mutations resistant to nucleosidic inhibitors of the viral reverse transcriptase (RT) derived from HIV-seropositive asymptomatic and untreated volunteer blood donors was examined. The RT amplicons of 32 specimens were analyzed by using a reverse hybridization line probe assay technique that detects resistance against zidovudine (3′-azido-3′-deoxythymidine [AZT], didanosine (2′,3′-dideoxyinosine [ddI], zalcitabine (2′,3′-dideoxycytidine [ddC]),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 21 publications
2
18
0
3
Order By: Relevance
“…Although lower overall prevalence of antiretroviral resistance has been previously reported in Brazil, 88 we should delineate high-risk and low-risk areas in order to analyze each separately. It is also of note that HIV-1 B/F recombinant strains have been fixed and expanded in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although lower overall prevalence of antiretroviral resistance has been previously reported in Brazil, 88 we should delineate high-risk and low-risk areas in order to analyze each separately. It is also of note that HIV-1 B/F recombinant strains have been fixed and expanded in this population.…”
Section: Discussionmentioning
confidence: 99%
“…91 In at least one Brazilian-based cross-sectional study of untreated individuals, possibly natural polymorphisms were found in nonsubtype B viruses, potentially affecting the response to nucleoside analogues. 88 To date, however, no prospective investigation of subtype B versus non-subtype B treatment responses, measuring potential confounding factors such as disease stage and medication adherence, has been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the beginning of the HAART era (1996–8), two studies conducted in Brazil [34], [35] showed an overall prevalence rate for transmitted resistance that ranged from 0.0% to 0.9%; resistance was mostly to NRTIs [34]. In 2001, a large study assessing data from eight different Brazilian states found an overall prevalence of 6.6%, with an uniform distribution among different drug classes (2.4% for NRTIs, 2.0% for NNRTIs and 2.2% for PIs) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that some subtype G strains have decreased susceptibility to PIs [36], [37]. In HIV-1 CRF01_AE infection, the RT mutations T69N and V75M were seen more frequently than in HIV-1 subtype B [38].…”
Section: Introductionmentioning
confidence: 63%